Determinants of Menu Acceptability in Indonesia’s Free Nutritious School Meal Program (MBG) among SD and SMP Students in North Jakarta - Mia Srimiati; Adhila Fayasari; Meisi Aspiran Telaumbauna; Ananda Gabriella (Sarana Ilmu Indonesia (Salnesia), 2026)
Indonesia’s Nutritious Meal Program (Makan Bergizi Gratis, MBG) is a school-based intervention aimed at improving students’ nutritional intake. The success of the program depends not only on menu quality but also on food acceptability, which influences actual consumption. This study aimed to analyze the determinants of MBG menu acceptability among elementary school (ES) and junior high school (JHS) students in North Jakarta. A cross-sectional study was conducted in two program-recipient schools, including ES (n=87) and JHS (n=73) students. Menu acceptability was assessed using a hedonic test, employing a 3-point scale for ES students and a 5-point scale for JHS students. Hedonic scores from ES students were linearly transformed to a 1–5 scale to enable comparability. Independent variables included nutrition knowledge, teacher support, household income, and eating habits (JHS only). Data were analyzed using the Mann–Whitney test, Chi-square test, and Poisson regression with robust variance to estimate prevalence ratios (PR) and adjusted prevalence ratios (APR). Results showed that overall acceptability scores were significantly higher among JHS than ES students (p < 0.001), while in ES, nutrition knowledge, teacher support, and household income showed no independent association with menu acceptability. In the JHS group, nutrition knowledge and eating habits were significantly associated with higher menu acceptability, while teacher support and household income were not significant in the final model. These findings indicated that determinants of menu acceptability differ by educational level. Tailored strategies to students’ development may improve school meals’ effectiveness in promoting healthy eating.